What Is 'Good Care' in a Medical/Surgical Setting? A Hermeneutic Phenomenological Study - Dewar, Janette (Auckland University of Technology, 2021)
This research explores the nature of ‘good’ care in medical/surgical wards. A Heideggerian, hermeneutic phenomenological philosophical and methodological approach was used. Heidegger’s philosophy privileges ontological inquiry concerned with uncovering human being in the everyday. There were 17 study participants: three past patients, three whānau members and 11 staff members from a range of disciplines including professional and auxiliary staff. Participants were interviewed and encouraged to tell stories that demonstrated ‘good care’. The stories of ‘good care’ revealed a depth of meaning that lies beneath the surface. The notion of how staff went about being themselves in the everyday became important. The way one responds and relates to others matters in ‘good care’. The ‘feeling’ of ‘good care’ was remembered by ex-patients as being important. Reflection on the stories of staff revealed a deep love for humanity. This love was felt and valued by patients. While difficult to describe, it was noticeable when absent. The notion of manaakitanga was demonstrated in the caring, mana-enhancing way in which care was experienced by patients. Notions of attunement and phronesis were revealed in the ability to recognise, understand and respond to the needs of others. An ability to authentically be-with another enabled staff-participants to see the needs of others and to ‘leap-in’ where needed or ‘leap-ahead’ to smooth the way for an experience of ‘good care’. There was a sense of the sacred in many of the stories. When ‘time-on-the-clock’ became dominant, ‘good care’ tended to retreat to the shadows. This study revealed that one’s comportment or way-of-being is central to bringing the various threads of ‘good care’ together. Thus noticing, developing and rewarding such comportment has implications for the recruitment and education of health care providers.
Keywords: Good care; Hospital; Comportment; Manaakitanga; Love; Attunement; Phronesis; Phenomenology